Application of Ginger Aromatherapy to Overcome Main Problems Post Operative Nausea and Vomiting (PONV) in Patients Post Appendictomy - Anisa Diyah Wiranti; Emah Marhamah; Kurniawan Bagus (Proceeding of the International Conference on Health Sciences and Nursing, 2024)
Background: Appendectomy is a type of surgical procedure appendicitis or the removal of an infected appendix. An appendectomy is performed because there is an infection in the appendix in the lower right quadrant of the abdomen or inflammation that occurs in the appendi. The impact of carrying out an appendectomy is PONV due to the anesthesia given. PONV causes discomfort in postoperative patients because it increases intra-abdominal pressure and increases blood pressure and the patient's heart rate. Objective: knowing that the application of ginger aromatherapy to post-appendectomy patients can decrease in Ms. G and Ms. M is experiencing nausea. Method: This research is a qualitative descriptive study with a case study approach, using 2 respondents, namely patients who experienced nausea in the Edelweis Room at TK II 04.05.01 Hospital, dr. Soedjono, Magelang City. Application is carried out 2 times a day for 3 consecutive days with an application time of 10 - 15 minutes, observing complaints of nausea pre and post implementation of the action. Results: Ginger aromatherapy can reduce complaints of post-appendectomy nausea through observing major and minor signs and symptoms regarding nausea in Ms. G and Ms. M with the same range, namely decreasing. Conclusion: The application of ginger aromatherapy is effective in reducing complaints of nausea in post-appendectomy patients.